2019
DOI: 10.1093/jn/nxy257
|View full text |Cite
|
Sign up to set email alerts
|

Apiaceous and Cruciferous Vegetables Fed During the Post-Initiation Stage Reduce Colon Cancer Risk Markers in Rats

Abstract: Previously, we found that cruciferous vegetables reduced colonic preneoplastic lesions (aberrant crypt foci; ACF) in rats when fed during both the initiation and post‐initiation stage of colon cancer. However, neither cruciferous vegetables nor another vegetable class, apiaceous vegetables, have been examined for a chemopreventive effect when fed only in the post‐initiation stage. The aim of our study was to determine the effect of apiaceous and cruciferous vegetables on ACF and markers of ACF dysplasia (SIM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…On the contrary, a higher intake of fresh, non-processed vegetables has been frequently associated with lower risks of some cancers such as breast [ 15 , 22 ] and colorectal [ 23 , 24 ] cancer and generally of cancers of the digestive tract [ 25 ]. Some in vitro studies have found that some compounds in some vegetables such as isothiocyanates (sulforaphane, glucoraphanin) and flavonoids (anthocyanidins, flavones, flavones) protect against the risk of carcinogenesis [ 23 , 26 , 27 ], consistent with these studies.…”
Section: Introductionsupporting
confidence: 67%
“…On the contrary, a higher intake of fresh, non-processed vegetables has been frequently associated with lower risks of some cancers such as breast [ 15 , 22 ] and colorectal [ 23 , 24 ] cancer and generally of cancers of the digestive tract [ 25 ]. Some in vitro studies have found that some compounds in some vegetables such as isothiocyanates (sulforaphane, glucoraphanin) and flavonoids (anthocyanidins, flavones, flavones) protect against the risk of carcinogenesis [ 23 , 26 , 27 ], consistent with these studies.…”
Section: Introductionsupporting
confidence: 67%
“…In addition to the epidemiological studies listed previously, other groups have attempted to confirm the protective effects of cruciferous vegetable consumption in vivo. Studies in rodent models of colorectal cancer have demonstrated the protective effects of including cruciferous vegetables in the diet by detecting a reduced formation of aberrant crypt foci in cruciferous vegetable-eating animals [ 45 , 46 ]. Furthermore, these studies have demonstrated that the protective effects are not recapitulated when other classes of vegetables are included in the diet in place of cruciferous vegetables.…”
Section: Organosulfur Compounds Derived From Cruciferous Vegetablesmentioning
confidence: 99%
“…© 2020 American Association for Cancer cancerpreventionresearch.aacrjournals.org Downloaded from was 65% lower in dimethylhydrazine (DMH)-treated animals fed a diet containing lycopene (300 ppm), a carotenoid found in tomatoes, as compared with those on a diet without lycopene (55). Recently, the effect of apiaceous and cruciferous vegetables on sialomucin-expressing and mucin-depleted ACF was examined in DMH-treated rats (56). Rats fed apiaceous vegetables (celery and parsnips) for 10 weeks developed approximately 20% fewer total dysplastic (sialomucinexpressing plus mucin-depleted) ACF, as compared with those fed a basal diet (P < 0.05).…”
Section: Preclinical Modelsmentioning
confidence: 99%